Farmer participatory adaptation and adoption of contour hedgerows for soil conservation - Fujisaka, Sam (International Center for Tropical Agriculture, 1998)
From 1987 through 1992 a team of on-farm researchers worked at Claveria in northern Mindanao to improve the productivity and sustainability of the local upland rice and maize-based agroecosystems. Adaptive research goals were to improve crop productivity, control soil erosion, and improve nutrient cycling. A "strategic" goal was to develop methods by which research programs could work with farmers to develop locally appropriate and adoptable innovations. We used contour hedgerow systems as a general technology to control soil erosion; worked with farmers on their adaptation of the technology; and eventually our results included lessons for farmer-participatory research, technology development, and technology transfer.